Novel compound C150 inhibits pancreatic cancer through induction of ER stress and proteosome assembly - Wang, Tao; Chen, Ping; Weir, Scott; Baltezor, Michael; Schoenen, Frank J.; Chen, Qi (Frontiers in Oncology, 2022)
Pancreatic cancer is a devastating disease with a dismal prognosis and poor treatment outcomes. Searching for new agents for pancreatic cancer treatment is of great significance. We previously identified a novel activity of compound C150) to inhibit pancreatic cancer epithelial to mesenchymal transition (EMT). Here we further revealed its mechanism of action. C150 induced ER stress in pancreatic cancer cells and subsequently increased proteasome activity by enhancing proteasome assembly, which subsequently enhanced the degradation of critical EMT transcription factors (EMT-TFs). In addition, as cellular responses to ER stress, autophagy was elevated, and general protein synthesis was inhibited in pancreatic cancer cells. Besides EMT inhibition, the C150-induced ER stress resulted in G2/M cell cycle arrest, which halted cell proliferation and led to cellular senescence. In an orthotopic syngeneic mouse model, an oral dose of C150 at 150 mg/kg 3x weekly significantly increased survival of mice bearing pancreatic tumors, reduced tumor growth and ascites occurrence. These results suggested that compound C150 holds promises in comprehensively inhibiting pancreatic cancer progression.